Cognitive Reserve Moderates the Association Between Cerebral Blood Flow and Language Performance in Older Adults with Mild Cognitive Impairment. (20th December 2022) - Brenner, Einat K; Edwards, Lauren; Thomas, Kelsey R.; Weigand, Alexandra J.; Edmonds, Emily C.; Bondi, Mark W.; Bangen, Katherine J.
Abstract: Background: It has consistently been demonstrated that individuals with higher cognitive reserve (CR) exhibit decreased risk for dementia, and differences in cerebral blood flow (CBF) among those with higher CR may offer a protective mechanism against the cognitive changes associated with dementia. We sought to investigate CR as a moderator of the effect of CBF on memory and language performance in patients with mild cognitive impairment (MCI) and those who are cognitively unimpaired (CU). Method: Older adults from the Alzheimer's Disease Neuroimaging Initiative (ADNI; N = 46 MCI, 101 CU) underwent neuropsychological evaluation and arterial spin labeling MRI, which was used to quantify CBF in a priori regions. Estimated VIQ from the American National Adult Reading Test was used as a CR proxy. Multiple linear regressions assessed for (1) effect of CR on cognition, (2) effect of CR on CBF, and (3) interaction between CR and CBF on cognition. Cognitive outcomes included memory (word list) and language (category fluency, naming). All models adjusted for age, gender, APOE e4 allele frequency, and education, and interactions additionally adjusted for baseline FDG and pulse pressure. Result: VIQ was not associated with memory but was positively associated with fluency and naming in both groups (ps<0.005). VIQ was not associated with CBF in either group. Individuals with MCI showed a significant interaction between VIQ and CBF on fluency across several regions, including the bilateral hippocampus ( p = 0.003), bilateral inferior temporal gyrus ( p = 0.008), superior frontal gyrus ( p = 0.005), and inferior frontal gyrus ( p <0.001). For all models, as CR increased, the magnitude of the association between CBF and performance increased. These interactions were not significant in the CU group. Models with naming or memory as the outcome variable were not significant in either group. Results remained similar when education was not adjusted for. Conclusion: These results suggest that among individuals with MCI, the association between CBF and category fluency is dependent on CR, even after adjusting for several factors. Specifically, higher CR may serve as a protective factor against the negative effect of CBF reductions on fluency. Further research is needed to clarify the role that CR plays as a moderator of CBF and cognition.